Tempeh Industry Wastewater Treatment using Mix Natural Adsorbents (Zeolite, Bentonite, Water Hyacinth-Activated Carbon): Effect of Mass Ratio and Dosage of Mix Adsorbents on Turbidity and pH - Lia Cundari; Muhammad Radhiy Sukandar; Fahmi Nurusman (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
Adsorption is the process of agglomeration of dissolved substances in solution by the surface of an absorbent substance which makes the material enter and collect in an absorbent substance. Natural adsorbents that function to treat tempe liquid waste are zeolite, bentonite, and water hyacinth activated carbon. The purpose of this study was to determine the effect of the mass ratio and dose of natural adsorbents on the turbidity and pH values of tempe wastewater. The mass ratio variation used was the ratio of each material in the form of zeolite: bentonite: active carbon of water hyacinth in the form of R1 (1:1:1); R2 (2:1:1); R3 (1:2:1); and R4 (1:1:2). The adsorbent dose carried out was 1.5 gr; 3 grams; and 4.5 gr per 100 ml volume of liquid waste. The contact time between the adsorbent and the liquid waste is every 15, 30, 60, 90, 120, 150 minutes. Processing of tempe liquid waste was carried out in laboratory-scale batches with 120 rpm stirring. The analysis was carried out in form of turbidity, pH, COD, BOD, and TSS. The results showed that the adsorption was able to reduce turbidity and increase the pH level up to 99% by stirring the mass ratio R2 (2:1:1) for 150 minutes with a dose of 4.5 grams. It was found that the turbidity value decreased from 520.5 NTU to 2.47 NTU =ncrease in pH levels reaching 75% at 150 minutes of stirring at a dose of 4.5 grams. Decreased pH value from 3.7 to 6.4. The maximum adsorption capacity validation results were obtained based on the Frendulinch analysis of 7.07-49.75 mg/g with a Freundlich constant of 0.67-0.70 at a dose of 4.5 grams.